Study on energy-saving operation of a combined heating system of solar hot water and air source heat pump. (1st February 2021) - Long, Jibo; Xia, Kuiming; Zhong, Huihui; Lu, Haolin; A, Yongga
Highlights: A dual heat source heat pump with solar hot water and air as heat source was designed. A hybrid solar hot water and air source heat pump combined heating system was proposed. The TRNSYS model of hybrid heating system was established. The diagram of the optimal energy efficiency area for different connection modes were drawn. The energy-saving property of hybrid heating system was verified. Abstract: In this work, a hybrid solar hot water and air source heat pump (HSAHP) combined heating system is proposed, which can realize various connection modes, such as solar hot water (SHW) and air source heat pump (ASHP) parallel heating mode, series heating mode, and preheating type connection mode of solar hot water as air source heat pump's heat source. In the cold season, the energy efficiency of the combined heating system was simulated and analyzed. The results showed that the solar radiation intensity and the ambient temperature are important factors that affect the energy efficiency of each connection method of the proposed combined heating system. In addition, the optimal energy efficiency area diagram of the HSAHP combined heating system was drawn, which showed the optimal energy efficiency area corresponding to the three connection modes (preheat air solar-air source heat pump (PASAHP), series, and parallel). The return water temperature as well as the area of the solar collectors can change the distribution of optimal energy efficiency area. Among the three connection modes, the change of backwater temperature has the greatest influence on the area of series mode and the least influence on the area of parallel mode. The change of solar collector area has the greatest influence on the area of parallel mode and the least influence on the area of PASAHP mode. The HSAHP combined heating system can obtain good energy-saving benefits by switching the connection mode of SHW and ASHP according to the outdoor weather conditions.